Melestarikan Madrasah Diniyah Non-Formal dalam Derasnya Dinamika Kehidupan Masyarakat Melalui Kegiatan Ekstrakurikuler di Desa Kotabedah Peleyan Kabupaten Situbondo - Mahmuda Mahmuda; Ahmad Musaddad (Proceedings of Annual Conference for Muslim Scholars, 2017)
This research aims to: 1) Know the condition of Miftahul Jannah religious schools, 2) know the supporting factors and obstacle factor and the constraints that exist in the field, 3) identify strategies that are relevant to the conditions of today's society. The results of this study indicate that: 1) between communities, schools, and goverment must work in synergy to improve the quality of religious schools and their sense of belonging so with the sense of belonging to evoke the spirit to participate in improving the quality of religious schools, 2) lack of special attention from the goverment in the form of a policy on any formal education institutions to refrain from any activity during a religious school learning activities take place, 3) lack of special attention from the goverment for the financial welfare of teachers and infrastructure of religious schools targeted, 4) to attract interest in learning the students then holding martial activities and badminton which has facilitated by fund comes from the local community, 5) lack of HRD in the madrasah diniyah management.Keywords: Madrasah Diniyah, Extracurricular.